A SURVEY ON ENVIRONMENTAL HEALTH CONDITION IN DISTRICT OF KANN, TEHRAN, IRAN - K. Imandel; M. Mohseni; F. Farzianpour (Tehran University of Medical Sciences, 1979)
In the first half of year 1972 a descriptive exploratory survey was done on 75 selected households in District of Kann comprising 589 people. Selection was carried out by simple random sampling without replacement. The study shows that 33% of men and women are in the age group of 15-24 and family dimension is 5.01. The difference in income level is high. More than 25% of the families earn less than 8500 tomans a year and 17.7% earn more than 25,000 tomans every year. 40% are illiterate and 6.7% are holding degrees above high school diploma. The average number of people living in a room is 2.2, which is above the standard given by Housing Health Committee of the U.S. Public Health Society (1.5 person in a room) but the average living space for a person is 7.5 m2 which is more than twice the recommended standard (3.6m2). In order to wash the dead bodies a place is determined but, since the people haven't been through the training course, it has not been used so far and the people in this area are using the water from stream and canal to wash the bodies as they would for dishes, vegetables and also taking a bath in summer. This may result in a health hazard. 22.6% of the children under age of 6 have diarrhea, 14% out of the above mentioned percentage is related to infants. Seven grab samples of drinking water were analyzed and the results were compared with the. International Standards for drinking water given by the W.H.O. It shows that the minimum M.P.N. and Fecal M.P.N. were 1350 and 900 per 100 m1 respectively. Therefore, it could be said that the drinking water (at the time of study) has been polluted by faeces and this implies that necessary measures should be taken before water is to be consumed for domestic purposes.